Assessing beverages consumption patterns of 11-14-year-old Aotearoa New Zealand children before, during, and after sport : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Muodza, Carol Ropafadzo (Massey University, 2023)
Background: Sports settings may be an important but understudied beverage consumption environment for children where there is evidence consumption of SSB such as sports drinks. This consumption is despite water being the only recommended beverage for exercising children. Aims: To review the existing literature on children’s habitual beverage consumption and beverage consumption in a sporting environment including factors that influence beverage consumption. To analyse novel data collected in the assessment of 11-14-year-old New Zealand (NZ) children’s beverage consumption before, during, and after organised sport and the influencing factors on beverage choice and compare the findings against current international literature. Methods: Articles for the literature review were found using Google Scholar, Scopus, and Massey University’s article database. Searches were limited between the years 2010 and 2022. A 13-item questionnaire was used to survey children in the upper north island region of NZ regarding their beverage consumption practices in a sporting environment. The questionnaire was based on the top 20 sports participated in by NZ children. The inclusion criteria were as follows: aged 11-14 years old, able to read and write in English, and played at least one game of organised sport. The participants’ self-reported beverage intake on the survey indicating what beverages they consumed up to 2 hours before, during, and up to 2 hours after sport. Results: Gender, age, and socioeconomic status (SES) were identified to influence milk, and sugar sweetened beverage consumption in literature. The same factors were found to influence beverage consumption in the present study. The mean age of the participants (n = 1339) was 12.1 (±0.9) years, 51.3% were female, 50.3% were European, 53.7% attended high decile ranking schools. Water (91.7%), sports drinks (25.7%), and milk (23.4%) were the top three consumed beverages. Water was consistently the leading beverage consumed by participants before (67.3%), during (70.6%), and after (51.1%) sport and if given the choice, participants would prefer to drink water for hydration (89.9%). Conclusion: Water was the most consumed and preferred beverage for this cohort of young sportspeople. Sports drinks were the next most consumed beverage overall, thus public health messaging is needed in sports settings for SSB such as sports drinks as there is no evidence to support their efficacy for children participating in exercise <60 min and that is not vigorous.
Keywords: beverage consumption; children; organised sport; motivations; beverage preferences; influences; 321006 Sport and exercise nutrition